2018
DOI: 10.1080/15592294.2018.1481703
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the histone demethylase KDM4B leads to activation of KDM1A, attenuates bacterial-induced pro-inflammatory cytokine release, and reduces osteoclastogenesis

Abstract: Periodontal disease (PD) afflicts 46% of Americans with no effective adjunctive therapies available. While most pharmacotherapy for PD targets bacteria, the host immune response is responsible for driving tissue damage and bone loss in severe disease. Herein, we establish that the histone demethylase KDM4B is a potential drug target for the treatment of PD. Immunohistochemical staining of diseased periodontal epithelium revealed an increased abundance of KDM4B that correlates with inflammation. In murine calva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…The lysine demethylase (KDM) 4 family of protein enzymes differ from FAD+ dependent protein enzymes in that they contain a JmjC-domain that requires Fe + , O 2 and 2-oxogluterate as cofactors to properly function [ 28 ]. This family of proteins have the ability to demethylate di- and tri- methyl histone 3 lysine 9 and 36 (H3K9 and H3K36, respectively) as well as histone 1.4 lysine 26 (H1.4K26) and trimethyl histone 3 lysine 56 (H3K56) [ 28 ]. It has been demonstrated that large quantities of KDM4B protein in areas of inflammatory infiltrate increases the number of osteoclasts present [ 28 ].…”
Section: Epigenetic Regulation By Histone Modificationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The lysine demethylase (KDM) 4 family of protein enzymes differ from FAD+ dependent protein enzymes in that they contain a JmjC-domain that requires Fe + , O 2 and 2-oxogluterate as cofactors to properly function [ 28 ]. This family of proteins have the ability to demethylate di- and tri- methyl histone 3 lysine 9 and 36 (H3K9 and H3K36, respectively) as well as histone 1.4 lysine 26 (H1.4K26) and trimethyl histone 3 lysine 56 (H3K56) [ 28 ]. It has been demonstrated that large quantities of KDM4B protein in areas of inflammatory infiltrate increases the number of osteoclasts present [ 28 ].…”
Section: Epigenetic Regulation By Histone Modificationsmentioning
confidence: 99%
“…This family of proteins have the ability to demethylate di- and tri- methyl histone 3 lysine 9 and 36 (H3K9 and H3K36, respectively) as well as histone 1.4 lysine 26 (H1.4K26) and trimethyl histone 3 lysine 56 (H3K56) [ 28 ]. It has been demonstrated that large quantities of KDM4B protein in areas of inflammatory infiltrate increases the number of osteoclasts present [ 28 ]. Additionally, in osteoclasts, it has been shown that the inhibition of KDM4B in pre-osteoclasts results in reduced osteoclastogenesis [ 28 ].…”
Section: Epigenetic Regulation By Histone Modificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 High expression of KDM4B has been reported to be correlated with inflammation and the inhibition of KDM4B, highlighting its potential as a novel therapeutic target for hyper-inflammatory diseases that gave rise to bone destruction. 15 A previous report indicated that KDM4B plays a vital role in lipolysis in adipose tissues. 16 DLX5 is an osteogenic gene and a negative regulator of adipogenesis.…”
Section: Introductionmentioning
confidence: 99%